The extracellular matrix protein EMILIN-1 impacts on the microenvironment by hampering gastric cancer development and progression - Capuano, Alessandra; Vescovo, Maddalena; Canesi, Simone; Pivetta, Eliana; Doliana, Roberto; Nadin, Maria Grazia; Yamamoto, Masami; Tsukamoto, Tetsuya; Nomura, Sachiyo; Pilozzi, Emanuela; Palumbo, Antonio; Canzonieri, Vincenzo; et al. (Gastric cancer : official journal of the International Gastric Cancer Association and the Japanese Gastric Cancer Association, 2024)
Background The contribution of the tumor microenvironment and extracellular matrix to the aggressive biology of Gastric Cancer (GC) has been recently characterized; however, the role of EMILIN-1 in this context is unknown. EMILIN-1 is an essential structural element for the maintenance of lymphatic vessel (LV) integrity and displays anti-proliferative properties as demonstrated in skin and colon cancer. Given the key role of LVs in GC progression, the aim of this study was to investigate the role of EMILIN-1 in GC mouse models. Methods We used the syngeneic YTN16 cells which were injected subcutaneously and intraperitoneally in genetically modified EMILIN-1 mice. In alternative, carcinogenesis was induced using N -Methyl- N -nitrosourea (MNU). Mouse-derived samples and human biopsies were analyzed by IHC and IF to the possible correlation between EMILIN-1 expression and LV pattern. Results Transgenic mice developed tumors earlier compared to WT animals. 20 days post-injection tumors developed in EMILIN-1 mutant mice were larger and displayed a significant increase of lymphangiogenesis. Treatment of transgenic mice with MNU associated with an increased number of tumors, exacerbated aggressive lesions and higher levels of LV abnormalities. A significant correlation between the levels of EMILIN-1 and podoplanin was detected also in human samples, confirming the results obtained with the pre-clinical models. Conclusions This study demonstrates for the first time that loss of EMILIN-1 in GC leads to lymphatic dysfunction and proliferative advantages that sustain tumorigenesis, and assess the use of our animal model as a valuable tool to verify the fate of GC upon loss of EMILIN-1.